Astrocyte Activation and the Calcineurin/NFAT Pathway in Cerebrovascular Disease - Kraner, Susan D.; Norris, Christopher M. (Frontiers in Aging Neuroscience, 2018)
Calcineurin (CN) is a Ca2+/calmodulin-dependent protein phosphatase with high abundance in nervous tissue. Though enriched in neurons, CN can become strongly induced in subsets of activated astrocytes under different pathological conditions where it interacts extensively with the nuclear factor of activated T cells (NFATs). Recent work has shown that regions of small vessel damage are associated with the upregulation of a proteolized, highly active form of CN in nearby astrocytes, suggesting a link between the CN/NFAT pathway and chronic cerebrovascular disease. In this Mini Review article, we discuss CN/NFAT signaling properties in the context of vascular disease and use previous cell type-specific intervention studies in Alzheimer’s disease and traumatic brain injury models as a framework to understand how astrocytic CN/NFATs may couple vascular pathology to neurodegeneration and cognitive loss.